Pengaruh parameter pemesinan dan komposisi campuran polyester - vinylester terhadap keutuhan permukaan silindris - Adam Malik (Jurnal Teknik Mesin Indonesia, 2022)
The surface integrity of the cylindrical machining is an absolute requirement for ready-to-assemble components. This deficiency causes the components to fail to be assembled. This is due to the contribution of various factors involved in producing a cylindrical surface. Especially on the cylindrical surface of components made of composite materials. This study reports the effect of lathe & drill parameters, polyester-vinylester blend composition on roundness, roughness, and changes in surface hardness, as well as the main contribution of these factors. This study aims to examine the influence and contribution of polyester-vinylester blend composition, feedrate, speed and depth of cut on roundness, roughness, and changes in surface hardness of lathe & drill products. To achieve this goal, a series of cylindrical surface machining experiments were carried out on workpieces of the polyester-vinylester blend of different compositions. In the experimental set, the Taguchi L9(4)3-OAs method was used. The experimental results show that the most influential on the roundness and surface roughness is the size of the composition of the polyester-vinylester blend followed by the size of the feedrate carried out. Cutting speed and depth of cut don't really matter. While the change in hardness that is very influential is the feed followed by the depth of cut, the composition of the mixture actually shows the opposite between lathe and drilling. The novelty obtained from this experiment is to obtain the desired surface integrity of the components made of composites by mixing composite matrix materials.